Unleashing inkjet-printed nanostructured electrodes and battery-free potentiostat for the DNA-based multiplexed detection of SARS-CoV-2 genes - Rossetti, Marianna (2024)
Following the global COVID-19 pandemic triggered by SARS-CoV-2, the need for rapid, specific and cost-effective point-of-care diagnostic solutions remains paramount. Even though COVID-19 is no longer a public health emergency, the disease still poses a global threat leading to deaths, and it continues to change with the risk of new variants emerging causing a new surge in cases and deaths. Here, we address the urgent need for rapid, cost-effective and point-of-care diagnostic solutions for SARS-CoV-2. We propose a multiplexed DNA-based sensing platform that utilizes inkjet-printed nanostructured gold electrodes and an inkjet-printed battery-free near-field communication (NFC) potentiostat for the simultaneous quantitative detection of two SARS-CoV-2 genes, the ORF1ab and the N gene. The detection strategy based on the formation of an RNA-DNA sandwich structure leads to a highly specific electrochemical output. The inkjet-printed nanostructured gold electrodes providing a large surface area enable efficient binding and increase the sensitivity. The inkjet-printed battery-free NFC potentiostat enables rapid measurements and real-time data analysis via a smartphone application, making the platform accessible and portable. With the advantages of speed (5 min), simplicity, sensitivity (low pM range, ∼450% signal gain) and cost-effectiveness, the proposed platform is a promising alternative for point-of-care diagnostics and high-throughput analysis that complements the COVID-19 diagnostic toolkit.